2013
DOI: 10.1590/s0034-71672013000400010
|View full text |Cite
|
Sign up to set email alerts
|

Desafiando medos: relatos de enfrentamento de usuários com transtornos fóbico-ansiosos

Abstract: This is an interpretative and comprehensive study that aimed to investigate ways of coping used by patients with phobic-anxious disorders, attended at the Centro de Atenção Psicossocial I, of the municipality of Queimadas, state of Paraíba, Brazil, in the period from October to December 2010. The empirical data were obtained through interviews and subjected to content analysis. From this material were extracted the main themes that formed the thematic category called CAPS I as a space to expression of subjecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
(16 reference statements)
0
2
0
2
Order By: Relevance
“…1 Millions of people suffer from any form of mental illness in the world, and its incidence is increasing progressively each year. 2 In Brazil, authors have revealed a high prevalence of these mental disorders in different studied populations. 3,4 The workers population is the most affected by this problem, since minor mental disorders affects about 30% of employed workers, and serious mental disorders, about 5 to 10%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Millions of people suffer from any form of mental illness in the world, and its incidence is increasing progressively each year. 2 In Brazil, authors have revealed a high prevalence of these mental disorders in different studied populations. 3,4 The workers population is the most affected by this problem, since minor mental disorders affects about 30% of employed workers, and serious mental disorders, about 5 to 10%.…”
Section: Introductionmentioning
confidence: 99%
“…5 Common Mental Disorder (CMD) was an expression created for anxiety, depression or somatoform symptoms, 6 which is currently found in the adult population, but little diagnosed in the health services. 2,3 Records of work-related diseases increased from 5,025 in 1988 to 30,334 in 2005 among workers in the general social security scheme. 7 Among the studies carried out with workers (teachers, rural workers, nurses, community agents, drivers and collectors), high prevalences of CMD were found.…”
Section: Introductionmentioning
confidence: 99%
“…Além de provocar sofrimento significativo, tais transtornos estão relacionados a elevados custos diretos e indiretos e estão entre os mais debilitantes transtornos psiquiátricos na vida adulta (3) , exigindo diagnóstico precoce e acompanhamento especializado (4) .…”
Section: Introductionunclassified
“…-ISSN 1981-ISSN -1179 Edição eletrônica em http://idonline.emnuvens.com.br/id problemas futuros.ParaAlmeida et al, (2013) pode-se dizer que o primeiro passo do tratamento é sensibilizar o paciente de que a fobia social é uma doença, e por isso pode e deve ser tratada, o que, geralmente, não é difícil, pois o sofrimento significativo torna esses pacientes receptivos à possibilidade de ajuda.1248 Id on Line Rev. Mult.…”
unclassified